2015
DOI: 10.5455/ijmsph.2015.20122014117
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nutritional status among elderly population in a rural area of West Bengal, India

Abstract: Background: Geriatric population is a potentially vulnerable group for malnutrition as per 2002 census of the World Health Organization. Objectives: To estimate the prevalence of malnutrition and risk of malnutrition among elderly population in Arkhali village,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
60
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 15 publications
17
60
7
Order By: Relevance
“…Results of this research indicate that about 31% of elders in the sample were at risk of malnutrition. This finding is somewhat low compared to the observed findings in the region; in an Indian study the rate was 60.4% and in an Iranian study conducted on the elderly living in nursing homes the rate was 38.7% (12,13). Further, no gender difference in the rate of malnutrition was observed in our study although many studies conducted on nutritional status of elders in South Asia had shown gender differences of nutritional status in the elderly (12)(13)(14).…”
Section: Discussioncontrasting
confidence: 56%
“…Results of this research indicate that about 31% of elders in the sample were at risk of malnutrition. This finding is somewhat low compared to the observed findings in the region; in an Indian study the rate was 60.4% and in an Iranian study conducted on the elderly living in nursing homes the rate was 38.7% (12,13). Further, no gender difference in the rate of malnutrition was observed in our study although many studies conducted on nutritional status of elders in South Asia had shown gender differences of nutritional status in the elderly (12)(13)(14).…”
Section: Discussioncontrasting
confidence: 56%
“…Similar finding was reported by Lahiri S et al whereas in studies done by Mohapatra SC et al, Mishra CP et al, Shankar R et al, Kritika et al, Chauhan P et al and Kumar R et al most of the elderly belongs to low socioeconomic status. 5,7,11,12,14,17,18 In present study, 48.64% of elderly were vegetarian while 51.36% were non vegetarian.…”
Section: Discussionmentioning
confidence: 46%
“…Mohapatra SC et al, Mishra CP et al, Kritika et al, Narapureddy B et al, Kumar R et al and Lahiri S et al confirmed the same. 5,7,12,13,[17][18][19] Most (92.5%) of the elderly lives in a joint family and similar observation were made by Mishra CP et al and Shankar R et al while Tirkey K et al and Kumar R et al found mostly elderly were living in nuclear families. 7,11,15,17 Majority of the elderly were illiterates (60%) in present study.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations